Little cigars and cigarillos harbor diverse bacterial communities that differ between the tobacco and the wrapper. - Suhana Chattopadhyay (PLoS ONE, 2019)
Despite their potential importance with regard to infectious and chronic diseases among tobacco users, microbial constituents of tobacco products lack characterization. Specifically, to our knowledge, there are no data describing the bacterial diversity of little cigars or cigarillos. To address this knowledge gap, we tested four brands of little cigars and cigarillos. Tobacco and wrapper subsamples (n = 132) were separately subjected to DNA extraction, followed by PCR amplification of the V3V4 hypervariable region of the 16S rRNA gene, and sequencing using Illumina HiSeq. Sequences were analyzed using QIIME and Phyloseq implemented in R. We identified 2,681 operational taxonomic units across all products. Significant differences in alpha and beta diversity were observed between Swisher Sweets and Cheyenne products. Alpha and beta diversity was also significantly different between tobacco and wrapper subsamples within the same product. Beta diversity analyses of only tobacco samples identified no significant differences in the bacterial microbiota of different lots of the same products; however, the microbiota in the wrapper differed significantly across lots for all brands. Overall, Firmicutes were found to dominate in the wrapper, whereas Proteobacteria were most abundant in the tobacco. At the genus level, Bacillus and Lactobacillus dominated in the wrappers, and Staphylococcus and Pseudomonas dominated in the tobacco. Our findings suggest that the bacterial microbiota of little cigars and cigarillos is diverse and differs significantly between the tobacco and the wrapper, and across brands. Future work is necessary to evaluate the potential public health implications of these findings.